Mapping Cucumber Vein Yellowing Virus Resistance in Cucumber (Cucumis sativus L.) by Using BSA-seq Analysis - Pujol, Marta; Alexiou, Konstantinos G.; Fontaine, Anne-Sophie; Mayor, Patricia; Miras, Manuel; Jahrmann, Torben; Garcia-Mas, Jordi; Aranda, Miguel A. (Frontiers in Plant Science, 2019)
Cucumber vein yellowing virus (CVYV) causes severe yield losses in cucurbit crops across Mediterranean countries. The control of this virus is based on cultural practices to prevent the presence of its vector (Bemisia tabaci) and breeding for natural resistance, which requires the identification of the loci involved and the development of molecular markers for linkage analysis. In this work, we mapped a monogenic locus for resistance to CVYV in cucumber by using a Bulked Segregant Analysis (BSA) strategy coupled with whole-genome resequencing. We phenotyped 135 F3 families from a segregating population between a susceptible pickling cucumber and a resistant Long Dutch type cucumber for CVYV resistance. Phenotypic analysis determined the monogenic and incomplete dominance inheritance of the resistance. We named the locus CsCvy-1. For mapping this locus, 15 resistant and 15 susceptible homozygous F2 individuals were selected for whole genome resequencing. By using a customized bioinformatics pipeline, we identified a unique region in chromosome 5 associated to resistance to CVYV, explaining more than 80% of the variability. The resequencing data provided us with additional SNP markers to decrease the interval of CsCvy-1 to 625 kb, containing 24 annotated genes. Markers flanking CsCvy-1 in a 5.3 cM interval were developed for marker-assisted selection (MAS) in breeding programs and will be useful for the identification of the target gene in future studies.